Randomized Control Trial of Functional Outcome between Instrumented Posterior Lumbar Interbody Fusion and Posterolateral Fusion in Degenerative and Isthmic Adult Spondylolisthesis.: Life Sciences-Spondylolisthesis - R, Dr. Venkatasubramanian; M, Manoharan; V, Venkatram; V, Ramkumar (International Journal of Life Science and Pharma Research, 2022)
Spondylolisthesis is a spinal condition that affects the lumbosacral vertebrae. This disease causes one of the lower vertebrae to slip forward onto the bone directly beneath it. It's a painful condition but treatable in most cases. Although spondylolisthesis can be asymptomatic, patients with degenerative and isthmic spondylolisthesis typically present with low back pain, neurologic symptoms, and/or radicular symptoms. The surgical treatment of spondylolisthesis is indicated for cases of neurogenic claudication, intractable radicular pain, severe low-back pain, presence of neurological symptoms, failure of conservative management, radiological instability, progressive worsening of the listheses, Meyerding grade III and IV listhesis, and spondylosis. The ideal surgical treatment remains controversial. We have compared the functional outcome following instrumented posterior lumbar interbody fusion and posterolateral fusion for adult spondylolisthesis in our study. The prospective study was conducted in the Department of Orthopaedics. A total of 30 patients who satisfied both the inclusion and exclusion criteria and gave informed consent were recruited for the study from January to December 2019. The patients were randomized into two groups. Of 30 patients, Group 1(n=18) underwent Posterior lumbar interbody fusion and Group 2 (n=12) underwent Posterolateral fusion. Random number generators were used for allotting the patients to the specified group. Using Oswestry Disability Index, Japanese Orthopaedic Association Score and Visual Analog Score were used for pre-operative and post-operative functional scoring. The mean age among those who received PLIF was 53.67 years and among those who received PLF was 55.17 years. Spondylolisthesis at L4-L5 comprised 66.7% among those who received PLIF and 58.3 % among those who received PLF. Neurological deficit was present in 66.7% of the participants who had received PLIF and 100% of the participants who have received PLF. Concerning those who had received PLIF as treatment, 11 patients had excellent and 7 patients had better outcome in PLIF group, 7 patients had excellent and 5 patient had better outcome in PLF group.. The mean JOAS pre-intervention score was 6.66 and 6.40 for PLIF and PLF groups, respectively. In the 6th month mean JOAS score of the PLIF group was 11.16 and that of the PLF group was 10.16. The pre-intervention mean VAS score was 6.44 and 6.50 for PLIF and PLF groups, respectively. In both, the groups over the follow-up period mean VAS score had shown a decreasing trend. Our study did not show any significant difference in functional outcome between both groups, however there seems to better short term (3 months) and mid-term (6 months) pain relief in PLIF group when compared to PLF group. Long term follow-up studies along with radiological outcome may help in establishing superiority between both procedures.